Implementation of a pragmatic approach in the Minna No Nihongo I - Indrowaty, Sri Aju; Dewi, Fitriana Puspita; Rahmawati, Femi Eka; Febrianda, Sony Difa; Fadila, Sinta (Universitas Mulawarman, 2024)
This research explores the theoretical aspects of implementing the pragmatic approach in learning speaking skills/kaiwa, as outlined in Minna No Nihongo 1's book. The pragmatic approach is a learning approach to improve students' speaking/kaiwa skills in the classroom, prioritizing contextualized learning of speaking skills. This emphasis on context becomes particularly significant throughout the learning process. By employing this approach, students, including those in secondary schools and universities, can closely simulate practical speaking conditions, both verbally and in written form. The method used is qualitative descriptive with purposive sampling. Therefore, applying the pragmatic approach has proven effective in promoting active learning, significantly improving students' speaking skills inside and outside the classroom. The Japanese language learning process should be designed to meet practical language needs that correspond to real-world situations. By incorporating patterns based on pragmatic studies, learners undergoing Japanese learning experiences will naturally connect with the practical aspects of communication in the language learning process.